ANTHROPOMETRIC INDICATORS AND DENTAL CARIES IN THE PEDIATRIC POPULATION OF RURAL COMMUNITIES IN THE PERUVIAN AMAZON: A CROSS-SECTIONAL STUDY - Aquino-Canchari, Christian Renzo (2025)
Introduction: Dental caries and nutritional alterations are common in childhood, particularly in rural communities with limited access to health services. Objective: To determine the association between anthropometric indicators and the presence of dental caries in children aged 5 to 11 years from selected rural communities in the Peruvian Amazon. Methods: Cross-sectional study including 116 children from Llaylla, Pampa Hermosa, and Belén (Satipo, Junín). Body mass index for age (BMI/A), abdominal circumference for age (AC/A), and height for age (H/A) were assessed according to WHO and MINSA standards. Dental caries was evaluated using the DMFT/dmft index and the clinical consequences of untreated dental caries (pufa/PUFA). Associations between anthropometric variables and dental caries were analyzed using logistic regression adjusted for age and sex, with p<0.05 considered statistically significant. Results: Children with overweight/obesity had a higher risk of caries in permanent dentition (OR=3.875) and a lower risk in primary dentition (OR=0.539). Those with high or very high risk according to AC/A showed OR=0.968 in permanent dentition and OR=0.864 in primary dentition. Children with low height for age (H/A) presented OR=1.319 in permanent dentition and OR=1.757 in primary dentition. All associations were not statistically significant (p>0.05). Conclusion: Dental caries is highly prevalent among Amazonian children. Anthropometric indicators were not significantly associated with caries, suggesting the influence of other factors such as diet and access to dental care.